A national study of neighbourhood access to gambling opportunities and individual gambling behaviour. Issue 10 (12th September 2008) - Pearce, J; Mason, K; Hiscock, R; Day, P
Abstract : Objective: To investigate associations between neighbourhood accessibility to gambling outlets (non-casino gaming machine locations, sports betting venues and casinos) and individual gambling behaviour in New Zealand. Design: A Geographical Information Systems (GIS) measure of neighbourhood access to gambling venues. Two-level logistic regression models were fitted to examine the effects of neighbourhood access on individual gambling behaviour after controlling for potential individual- and neighbourhood-level confounding factors. Setting: 38 350 neighbourhoods across New Zealand. Participants: 12 529 respondents of the 2002/03 New Zealand Health Survey. Results: Compared with those living in the quartile of neighbourhoods with the furthest access to a gambling venue, residents living in the quartile of neighbourhoods with the closest access were more likely (adjusted for age, sex, socio-economic status at the individual-level and deprivation, urban/rural status at the neighbourhood-level) to be a gambler (OR 1.60, 95% CI 1.20 to 2.15) or problem gambler (OR 2.70, 95% CI 1.03 to 7.05). When examined independently, neighbourhood access to venues with non-casino gaming machines (gambling: OR 1.67, 95% CI 1.28 to 2.18; problem gambling: OR 2.71, 95% CI 1.45 to 5.07) and sports betting venues (gambling: OR 1.67, 95% CI 1.28 to 2.18; problem gambling: OR 2.71, 95% CI 1.45 to 5.07) were similarly related. Conclusions: Neighbourhood access to opportunities for gambling is related to gambling and problem gambling behaviour, and contributes substantially to neighbourhood inequalities in gambling over and above-individual level characteristics.